Novel composite metal material

By using a combined structure of metal material layer, antioxidant layer, nanolayer and protective layer in composite metal materials, the problems of vulnerability and health hazards of existing composite metal materials are solved, and higher stress strength and corrosion resistance are achieved , prolongs service life and reduces health hazards.

CN119239071AInactive Publication Date: 2025-01-03XIGANG INTELLIGENT MANUFACTURING (WUXI) GENERAL EQUIPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411253628.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing composite metal materials are prone to damage during use, lacking mechanical properties, ductility and corrosion resistance, which may cause harm to the health of users.

Method used

A new composite metal material structure consisting of a metal material layer, an oxidation layer, a nanolayer and a protective layer are adopted. The metal material layer includes titanium, aluminum, magnesium, sodium molybdate, copper, boron nitride and zinc. The protective layer is made of stainless steel The material is composed of 60-65%, 10-15%, 10-15%, and 10-15%.

Benefits of technology

The overall stress and heat resistance strength are improved, and the protective layer effectively reduces the generation of scratches and rust, improves the service life and safety of the material, and avoids the harm of toxic substances to health.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a novel composite metal material, and relates to the technical field of composite metal. The metal material layer, the anti-oxidation layer and the nanometer layer can be protected under the action of the protection layer, then the actual effect can be guaranteed, the overall stress strength can be improved under the action of the metal material layer, and the anti-oxidation purpose can be achieved under the action of the anti-oxidation layer; by arranging the nanometer layer, internal materials can be effectively blocked, and toxic substances possibly generated in the production process of the device are prevented from damaging the body health of a user; the protective layer is made of stainless steel materials, the protective layer can effectively protect internal materials, the phenomena such as scratches generated outside the device can be effectively reduced in the using process, and meanwhile rust is effectively reduced. The heat-resistant strength, the low-temperature toughness and the fracture toughness can be improved; the hardness is improved, the softness is improved, and breakage is not prone to occurring; the overall corrosion inhibition effect is improved, and the overall service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite metals, and in particular to a new type of composite metal material. Background Art

[0002] Composite metal materials refer to the general term for materials with metal properties that are composed mainly of metal elements or metal elements. They include pure metals, alloys, composite metal materials, intermetallic compounds, and special composite metal materials. Composite materials are a mixture. They have played a great role in many fields and replaced many traditional materials. Composite materials are divided into metal-metal composite materials, non-metal-metal composite materials, and non-metal-non-metal composite materials according to their composition. Compared with ordinary single-reinforced composite materials, their impact strength, fatigue strength, and fracture toughness are significantly improved, and they have special thermal expansion properties.

[0003] Existing composite materials pursue hardness during use, but lack mechanical properties, ductility and corrosion resistance. They are easily damaged during use, and some composite metal materials may even harm the health of users during use. For this reason, we propose a new type of composite metal material. Summary of the invention

[0004] The purpose of the present invention is to solve the problems mentioned in the above background technology, and the present invention provides a new type of composite metal material.

[0005] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions:

[0006] A new type of composite metal material comprises, from top to bottom, a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0007] Furthermore, the metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60-65%, 10-15%, 10-15%, 10-15%.

[0008] Furthermore, the metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60%, 15%, 15% and 10%.

[0009] Furthermore, the metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 65%, 10%, 10%, and 15%.

[0010] Furthermore, the metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 62.5%, 12.5%, 12.5%, and 12.5%.

[0011] Furthermore, the metal material layer includes the following components and the weight percentage of each component is: titanium 0.3-1.3%, aluminum 20-30%, magnesium 1-2.5%, sodium molybdate 3-7%, copper 2-4%, boron nitride 1-4%, metal carbide 2-10%, zinc 5-7%, and the rest is iron.

[0012] Furthermore, the metal material layer includes the following components and the weight percentage of each component is: 1.3% titanium, 20% aluminum, 1% magnesium, 3% sodium molybdate, 2% copper, 1% boron nitride, 2% metal carbide, 5% zinc, and the rest is iron.

[0013] Furthermore, the metal material layer includes the following components and the weight percentage of each component is: 0.3% titanium, 30% aluminum, 2.5% magnesium, 7% sodium molybdate, 4% copper, 4% boron nitride, 10% metal carbide, 7% zinc, and the rest is iron.

[0014] Furthermore, the metal material layer includes the following components and the weight percentage of each component is: 0.8% titanium, 25% aluminum, 1.75% magnesium, 5% sodium molybdate, 3% copper, 2.5% boron nitride, 6% metal carbide, 6% zinc, and the rest is iron.

[0015] Furthermore, the protective layer is made of stainless steel.

[0016] The beneficial effects of the present invention are as follows:

[0017] 1. The present invention can protect the metal material layer, the anti-oxidation layer and the nano layer under the action of the protective layer, thereby ensuring the actual effect. The overall force strength can be improved under the action of the metal material layer, and the anti-oxidation purpose can be achieved under the action of the anti-oxidation layer. By setting the nano layer, the internal material can be effectively blocked to avoid the toxic substances that may be produced during the production process of the device from damaging the health of the users. The protective layer is made of stainless steel, and the protective layer can effectively protect the internal material. During use, scratches and the like on the outside of the device can be effectively reduced, and rust can be effectively reduced.

[0018] 2. The metal material layer of the present invention includes the following components: titanium, aluminum, magnesium, sodium molybdate, copper, boron nitride, metal carbide and zinc, which can improve heat resistance, low-temperature toughness and fracture toughness; while improving hardness, it also improves softness and will not break easily; it improves the overall corrosion inhibition effect and the overall service life. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention.

[0020] The present invention provides a new type of composite metal material, which comprises, from top to bottom, a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0021] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60-65%, 10-15%, 10-15%, and 10-15%.

[0022] The metal material layer includes the following components and the weight percentage of each component is: titanium 0.3-1.3%, aluminum 20-30%, magnesium 1-2.5%, sodium molybdate 3-7%, copper 2-4%, boron nitride 1-4%, metal carbide 2-10%, zinc 5-7%, and the rest is iron.

[0023] Under the action of the protective layer, the metal material layer, the anti-oxidation layer and the nano layer can be protected, thereby ensuring the actual effect. Under the action of the metal material layer, the overall force strength can be improved, and under the action of the anti-oxidation layer, the anti-oxidation purpose can be achieved. By setting up a nano layer, the internal material can be effectively blocked to avoid toxic substances that may be produced during the production process of the device from damaging the health of users. The protective layer is made of stainless steel, and the protective layer can effectively protect the internal material. During use, it can effectively reduce scratches and other phenomena on the outside of the device, and effectively reduce rust.

[0024] The metal material layer includes the following components: titanium, aluminum, magnesium, sodium molybdate, copper, boron nitride, metal carbide, zinc, and the rest is iron.

[0025] Titanium alloy has good heat resistance, low temperature toughness and fracture toughness; aluminum can increase hardness while increasing softness and will not break easily; magnesium has good lightness, cutting properties, corrosion resistance, shock absorption, dimensional stability and impact resistance, which are far superior to other materials, that is, it can effectively improve the actual use effect and service life; sodium molybdate can improve the overall corrosion inhibition effect and increase the overall service life; copper has good ductility, high thermal conductivity and electrical conductivity, and the alloy made from it also has good mechanical properties and very low resistivity; boron nitride has the characteristics of ultra-high temperature resistance and still maintains superior lubrication performance under high temperature conditions , non-toxic, non-polluting, highly environmentally friendly, highly chemically inert, extremely low friction coefficient, high pressure resistance, high resistance, thermal shock resistance, corrosion resistance, and good thermal conductivity; metal carbides are resistant to high temperatures, wear resistance, corrosion resistance, and have good electrical conductivity, which can improve the overall use effect and service life; zinc galvanizing has excellent resistance to atmospheric corrosion, and a protective film is easily formed on the surface at room temperature. The steel products are treated with anti-corrosion by galvanizing to extend their service life. The strength and hardness of zinc itself are not high, but after adding alloy elements such as aluminum and copper, its strength and hardness are greatly improved, which can effectively improve the overall strength and hardness.

[0026] Example 1

[0027] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0028] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60%, 15%, 15% and 10%.

[0029] The metal material layer includes the following components and the weight percentage of each component is: titanium 1.3%, aluminum 20%, magnesium 1%, sodium molybdate 3%, copper 2%, boron nitride 1%, metal carbide 2%, zinc 5%, and the rest is iron.

[0030] Example 2

[0031] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0032] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60%, 15%, 15% and 10%.

[0033] The metal material layer includes the following components and the weight percentage of each component is: 0.3% titanium, 30% aluminum, 2.5% magnesium, 7% sodium molybdate, 4% copper, 4% boron nitride, 10% metal carbide, 7% zinc, and the rest is iron.

[0034] Example 3

[0035] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0036] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60%, 15%, 15% and 10%.

[0037] The metal material layer includes the following components and the weight percentage of each component is: titanium 0.8%, aluminum 25%, magnesium 1.75%, sodium molybdate 5%, copper 3%, boron nitride 2.5%, metal carbide 6%, zinc 6%, and the rest is iron.

[0038] Example 4

[0039] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0040] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60%, 15%, 15% and 10%.

[0041] The metal material layer includes the following components and the weight percentage of each component is: titanium 1.3%, aluminum 20%, magnesium 1%, sodium molybdate 3%, copper 2%, boron nitride 1%, metal carbide 2%, zinc 5%, and the rest is iron.

[0042] Example 5

[0043] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0044] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60%, 15%, 15% and 10%.

[0045] The metal material layer includes the following components and the weight percentage of each component is: 0.3% titanium, 30% aluminum, 2.5% magnesium, 7% sodium molybdate, 4% copper, 4% boron nitride, 10% metal carbide, 7% zinc, and the rest is iron.

[0046] Example 6

[0047] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0048] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60%, 15%, 15% and 10%.

[0049] The metal material layer includes the following components and the weight percentage of each component is: titanium 0.8%, aluminum 25%, magnesium 1.75%, sodium molybdate 5%, copper 3%, boron nitride 2.5%, metal carbide 6%, zinc 6%, and the rest is iron.

[0050] Example 7

[0051] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0052] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 62.5%, 12.5%, 12.5%, and 12.5%.

[0053] The metal material layer includes the following components and the weight percentage of each component is: titanium 1.3%, aluminum 20%, magnesium 1%, sodium molybdate 3%, copper 2%, boron nitride 1%, metal carbide 2%, zinc 5%, and the rest is iron.

[0054] Example 8

[0055] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0056] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 62.5%, 12.5%, 12.5%, and 12.5%.

[0057] The metal material layer includes the following components and the weight percentage of each component is: titanium 0.3-1.3%, aluminum 20-30%, magnesium 1-2.5%, sodium molybdate 3-7%, copper 2-4%, boron nitride 1-4%, metal carbide 2-10%, zinc 5-7%, and the rest is iron.

[0058] Example 9

[0059] From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

[0060] The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 62.5%, 12.5%, 12.5%, and 12.5%.

[0061] The metal material layer includes the following components and the weight percentage of each component is: titanium 0.8%, aluminum 25%, magnesium 1.75%, sodium molybdate 5%, copper 3%, boron nitride 2.5%, metal carbide 6%, zinc 6%, and the rest is iron.

[0062] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A new type of composite metal material, characterized in that: From top to bottom, it includes: a metal material layer, an anti-oxidation layer, a nano layer and a protective layer, wherein the metal material layer, the anti-oxidation layer and the nano layer are connected in sequence from bottom to top, and the protective layer is coated on the outside of the metal material layer, the anti-oxidation layer and the nano layer.

2. A new composite metal material according to claim 1, characterized in that: The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60-65%, 10-15%, 10-15%, 10-15%。 3. A new composite metal material according to claim 1, characterized in that: The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 60%, 15%, 15% and 10%.

4. A new composite metal material according to claim 1, characterized in that: The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 65%, 10%, 10% and 15%.

5. A new composite metal material according to claim 1, characterized in that: The metal material layer, the anti-oxidation layer, the nano layer and the protective layer are composed in the following proportions: 62.5%、12.5%、12.5%、12.5%。 6. A new composite metal material according to claim 1, characterized in that: The metal material layer includes the following components and the weight percentage of each component is: titanium 0.3-1.3%, aluminum 20-30%, magnesium 1-2.5%, sodium molybdate 3-7%, copper 2-4%, boron nitride 1-4%, metal carbide 2-10%, zinc 5-7%, and the rest is iron.

7. A new composite metal material according to claim 1, characterized in that: The metal material layer includes the following components and the weight percentage of each component is: 1.3% titanium, 20% aluminum, 1% magnesium, 3% sodium molybdate, 2% copper, 1% boron nitride, 2% metal carbide, 5% zinc, and the rest is iron.

8. The novel composite metal material according to claim 1, characterized in that: The metal material layer includes the following components and the weight percentage of each component is: 0.3% titanium, 30% aluminum, 2.5% magnesium, 7% sodium molybdate, 4% copper, 4% boron nitride, 10% metal carbide, 7% zinc, and the rest is iron.

9. A new composite metal material according to claim 1, characterized in that: The metal material layer includes the following components and the weight percentage of each component is: 0.8% titanium, 25% aluminum, 1.75% magnesium, 5% sodium molybdate, 3% copper, 2.5% boron nitride, 6% metal carbide, 6% zinc, and the rest is iron.

10. A new composite metal material according to claim 1, characterized in that: The protective layer is made of stainless steel.